Small scale sport events in Covid 19 pandemic era: a sustainable business perspective / Mageswari Ranjanthran, Arivalagan Ponniyah and Susela Devi K Suppiah - Ranjanthran, Mageswari; Ponniyah, Arivalagan; K Suppiah, Susela Devi (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
As the number of sports-related tourists grows worldwide, events-based tourism has been developing as one of the fast-growing tourism attractions. The elements that have attracted sports tourists to participate in events have a connection to tourism attraction value. On the other hand, the organizer of Small-Scale Sports Events (SSSE) has a social obligation to organise these events from a sustainable business perspective considering economic, environmental and social considerations. Although, countless sports tourism events have been organized globally, there is limited understanding of the sustainable practices that drive these events. There is a potential impact of the SSSE towards the environment and the communities. The SSSE, defined as normal season or a small unique sports events which provide the residents with more advantage, faces challenges to ensuring sustainability in organizing these sports events. However, small-scale events can be a form of sustainable tourism for communities. Further, these events portfolio can contribute to the growth o f a society and nation holistically. The purpose of this paper is to critically review and synthesis extant literature, on management and organization of small-scale sports events for the last ten years, to develop a conceptual model for sustainable business for SSSE. This paper focuses on the conceptualization and implementation of SSSE and sustainable tourism which covers the theory and principles of event tourism, strategies and implementation of sustainability practices in event organizing on karate related events. Self-realization and self-improvement through martial arts are the motives of martial arts tourism which are the supportive factors for SSSE for organizing events. The issues and challenges, and the roles of stakeholders are discussed in-depth to create the balance for practical and theoretical paradigms. Further, the critical insights from the literature provides input for framing notions of sustainable business for sports tourism event organisers. The conceptual model will guide the SSSE in Malaysia to balance aspects of tourism and sustainable business practices to achieve sustainability.